Excellent teachers' thinking model: implications for effective teaching - Hamzah, Mohd Sahandri Gani; Mohamad, Hapidah; Ghorbani, Mohammad Reza (Edith Cowan University, 2008)
This study aimed to suggest an Excellent Teacher Thinking Model that has the potential to be utilized in the development of excellent teachers. Interaction survey method using survey questions, observation, document review and interview was conducted in this study. One hundred and five excellent teachers were selected randomly as research respondents. Two sets of instrument constructed and used in this study were Teachers’ Thinking questionnaire and Teachers’ Teaching Performance observation form. Cronbach Alpha reliability value was between 0.73-0.92 for every component in each division. Multiple regression analysis (stepwise) was used to answer the research questions. R square value (R2 = 0.31) showed that the overall contribution of the two significant variables (expectations and subject expertise) to teaching performance was 31.10 percent. The linear regression equation was Y = 40.30 + 13.39 (Expectations) - 1.37 (Subject Expertise). Excellent Teacher Thinking Model generated from this study showed that all five components of thinking domain contributed significantly to excellent teachers’ teaching performance. Among the five thinking components, teacher expectation showed the highest contribution to excellent teacher teaching performance. This study showed that teacher expectations play a vital role in shaping the objectives, goals, curriculum, and instructional methods of schools. Hence, excellent teachers’ professional development programs will help school teachers improve the profession.